205 Tractography Characterizing Lesions Differentiating Responders to Stereotactic Capsulotomy for Obsessive-Compulsive Disorder. (August 2016) - Nanda, Pranav; Banks, Garrett P.; Pathak, Yagna; Paulo, Danika L.; Horga, Guillermo; Hoexter, Marcelo Q.; Xu, Zhiyuan; Lopes, Antonio; McLaughlin, Nicole; Greenberg, Benjamin; Sheehan, Jason P.; Miguel, Euripides C.; et al.
Abstract : INTRODUCTION: Whereas most patients with obsessive-compulsive disorder (OCD) are well controlled with pharmacological and cognitive behavioral therapy, 10% to 20% remain severe and refractory. Stereotactic lesions in the anterior limb of the internal capsule (ALIC) have been used for decades to treat these patients. Recent studies using stereotactic radiosurgery (SRS) have demonstrated significant symptom response in 30% to 70% of patients. One contributor to response variability may be differences in upstream and downstream brain regions affected by lesions. We used diffusion tensor imaging to examine networks affected by successful and unsuccessful targets. METHODS: We analyzed 39 postoperative volumetric T1-MRIs from 22 patients with refractory OCD who underwent SRS capsulotomy at 4 institutions. Data were analyzed by using a voxel-based generalized linear model to identify an area predicting response status. Using an atlas incorporating diffusion data from 842 Human Connectome Project controls, we identified fiber tracts originating from a seed of average lesion size centered on this predictive area ("predictive seed"). We also tested an identically sized dorsal and posterior seed ("posterior seed"). RESULTS: The statistical model identified a right ALIC region (near the mid-putaminal line in the axial plane and near the ventral-most ALIC in the coronal plane) differentiating responders from nonresponders. The predictive seed exhibited connections with right orbitofrontal cortex (OFC) and thalamus. The posterior seed connected with right rostral prefrontal cortex and thalamus. CONCLUSION: SRS capsulotomy remains attractive for severe, refractory OCD. This retrospective analysis shows that lesions including ventral right ALIC will more likely produce clinical response. Lesions here modulate a network connecting right OFC and thalamus, supporting the hypothesis that aberrant frontal cortico-basal-thalamo-cortical positive feedback loops may underlie OCD. The absence of posterior seed fiber tracts terminating in OFC underscores OFC's importance in OCD. Prospective longitudinal imaging collection will help validate our understanding of the affected network, permit individualized analyses, and improve this approach's efficacy.